Design and experimental force analysis of a novel elliptical vibration assisted orthopedic oscillating saw. (April 2018) - Shu, Liming; Sugita, Naohiko; Oshima, Masaya; Mitsuishi, Mamoru
Highlights: We designed a novel elliptical vibration assisted orthopedic oscillating saw to achieve a low cutting force under the condition of deepening cut depth and reducing cutting speed. A kinematical analysis was performed on the elliptical vibration assisted orthopedic oscillating saw. Elliptical vibration assisted sawing exhibited a smaller principle force and thrust force than conventional sawing. The cutting forces are significantly reduced by increasing vibration frequency and vibration amplitude, and decreasing the sawing speed in current design. Abstract: Orthopedic oscillating saws (OOSs) are widely used for plane processing in orthopedic surgery such as knee and hip replacement. However, sawing has been associated with bone breakthrough and necrosis problems. In this paper, a novel elliptical vibration assisted OOS was designed to achieve a low cutting force under the condition of deepening cut depth and reducing cutting speed, based on the analysis of brittle fractures of the bone and elliptical vibration assisted cutting kinematics. The elliptical vibration was generated using two parallel stacked piezoelectric actuators assembled with the fixture. In order to reduce the large cutting forces due to the large cutting depth, a series of experiments was also conducted to investigate the influence of processing parameters on cutting forces. It was demonstrated that cutting forces are significantly reduced by increasing the vibration frequency and vibration amplitude, and decreasing the sawing speed in the current design. The new design could minimize the cutting forces during sawing and allow surgeons to have better control over the sawing process.